INNER WORLD AS SUBJECTIVE REALITY OF THE PERSON - Alexey V. Lukyashchenko (Статистика и экономика)
The article considers the methodological foundations of the study of man's inner world. The main attention is focused on the problem of functioning of the human inner world as «fields» realization of human subjectivity, the definition of the space in which «lives» the sovereign human I. Attempts to prove that the inner world of man cannot be reduced only to the world of human consciousness, the world of human feelings, thoughts, emotions and experiences are made. Dialectic analysis of external and internal, subjective and objective leads to an understanding of human subjectivity as the world objectificated essential forces of the human being, the world of human culture.